Functionalized Vesicles with Co‐Embedded CdSe Quantum Dots and [FeFe]‐Hydrogenase Mimic for Light‐Driven Hydrogen Production. Issue 7 (19th May 2016) - Troppmann, Stefan; König, Burkhard
Abstract: A photocatalytic hybrid system for the production of hydrogen in purely aqueous solution was prepared by the co‐embedding of hydrophobic oleic acid capped CdSe quantum dots (QD) for light harvesting and an amphiphilic [FeFe]‐hydrogenase subunit mimic for proton reduction into phospholipid vesicle membranes. These bio‐inspired functionalized vesicles concentrate the catalytic subunits in close proximity and show light‐driven hydrogen generation in the presence of ascorbic acid resulting in 651 and 2.47 x 10 5 catalytic turnovers for the membrane‐incorporated catalyst and the QDs, respectively. Abstract : Functionalized membranes with quantum dots (QD) as chromophores and [FeFe]‐H2 ase subunit mimics as proton reduction catalysts (Cat) show light‐driven hydrogen generation in purely aqueous solution.